2014
DOI: 10.1371/journal.pone.0093473
|View full text |Cite
|
Sign up to set email alerts
|

Apelin Increases Cardiac Contractility via Protein Kinase Cε- and Extracellular Signal-Regulated Kinase-Dependent Mechanisms

Abstract: BackgroundApelin, the endogenous ligand for the G protein-coupled apelin receptor, is an important regulator of the cardiovascular homoeostasis. We previously demonstrated that apelin is one of the most potent endogenous stimulators of cardiac contractility; however, its underlying signaling mechanisms remain largely elusive. In this study we characterized the contribution of protein kinase C (PKC), extracellular signal-regulated kinase 1/2 (ERK1/2) and myosin light chain kinase (MLCK) to the positive inotropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 58 publications
(97 reference statements)
3
59
0
5
Order By: Relevance
“…The predominant isoform in the human cardiovascular system is [Pyr 1 ]apelin-13 [3]. Infusion of apelin leads to vasodilatation, in humans in vitro [3] and in vivo [4] and in rodents in vivo [5], as well as cardiac inotropy in vitro [3], [6], [7] and in vivo in rats [8], [9], [10], mice [11] and humans [12] without hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…The predominant isoform in the human cardiovascular system is [Pyr 1 ]apelin-13 [3]. Infusion of apelin leads to vasodilatation, in humans in vitro [3] and in vivo [4] and in rodents in vivo [5], as well as cardiac inotropy in vitro [3], [6], [7] and in vivo in rats [8], [9], [10], mice [11] and humans [12] without hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis found support when measurements of the sarcomere shortening in isolated cardiomyocytes showed that the positive inotropic effect was not accompanied by any increase in Ca 2+ concentration [17,85]. Recently, Perjés et al [75] demonstrated that the raises in myofilament Ca 2+ sensitivity and cross-bridge kinetics is due to the phosphorylation of regulatory myosin light chain (RMLC) via myosin light chain kinase (MLCK) (Fig. 3).…”
Section: Inotropic Effectmentioning
confidence: 84%
“…A short lasting inotropic effect was also seen in isolated adult rat cardiomyocytes, where the sarcomere shortening increased for 1 -2 min only in response to apelin-16 superfusion (1-10 nM) and returned to the control before the superfusion was discontinued [17]. The different duration of the effect does not seem to be depend on the different isoforms, because (pyr)apelin-13, apelin-13 and apelin-36 show comparable potency and efficacy in inducing positive inotropic effect [8,75]. On the other hand the importance of different procedures of contractility assessment cannot be disregarded.…”
Section: Inotropic Effectmentioning
confidence: 88%
See 1 more Smart Citation
“…37 The observation that b-blockers or angiotensin II receptor antagonists (ARBs), both cornerstones of contemporary disease-modifying HF therapy, do not attenuate apelin-induced inotropy is notable should apelin supplementation go on to become a realistic therapeutic goal in HF. 37 Crucially, apelin appears to exert its inotropic effects by increasing myofilament sensitivity to calcium without exerting the potentially deleterious effects of increasing intracellular cyclic adenosine monophosphate or calcium concentrations, 38,39 both of which are thought to account for the arrhythmogenic potential of established inotropic agents. No inotrope to date has been shown to improve outcomes in acute decompensated HF.…”
Section: Effects Of Exogenous Apelin On the Normal Heartmentioning
confidence: 99%